Investigation of the Magnesium Oxide Nanoparticles Effect on Thyroid (T3, T4) Thyroid Stimulating Hormones (TSH) in Rat - H. Obaid, Alieaa; A. Abbas, Salma; M. Hussein, Fadhila; A. Jawad, Asmaa; A. Ibrahim, Tahseen; H. Obaeed, Nareen (Al-Nahrain Journal of Science, 2022)
Nanoparticles (NPs) are used in industrial and biomedical fields such as cosmetics, food additives and biosensors. One of the most important of these particles is magnesium oxide nanoparticles. The nanoparticles of magnesium oxide are diagnosed through several techniques, including the Atomic Force Microscope (AFM) and (XRD). Analyzing the structure of studied nano materials is useful to investigate their medical applications by influencing thyroid hormones such as thyroxine (T4), triiodothyronine (T3), and thyroid-stimulating hormone (TSH) in rat. A total of 15 Sprague-Dawley adult female rats were split into three groups, each group injected daily intraperitoneally of MgONPs at one dose (80 mg/kg). In different periods (14 and 28 days), as follows; The first group: is the control group without injections. The second group: injected intraperitoneally with MgONPs (80 ppm) for 14 days. The third group: was injected intraperitoneally with MgO NPs (80 ppm) for 28 days. The findings of this study revealed a highly significant reduction (p < 0.01) in T3, T4 and Thyroid stimulating hormones (TSH) levels increased high significantly (p < 0.01).